2018
DOI: 10.1039/c7nr09591k
|View full text |Cite
|
Sign up to set email alerts
|

Towards substrate engineering of graphene–silicon Schottky diode photodetectors

Abstract: Graphene-Silicon Schottky diode photodetectors possess beneficial properties such as high responsivities and detectivities, broad spectral wavelength operation and high operating speeds. Various routes and architectures have been employed in the past to fabricate devices. Devices are commonly based on the removal of the silicon-oxide layer on the surface of silicon by wet-etching before deposition of graphene on top of silicon to form the graphene-silicon Schottky junction. In this work, we systematically inve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 63 publications
2
36
0
Order By: Relevance
“…3c shows the J light , J light /J dark ratio, and LDR for various P in values at zero-bias and 77 K. The device exhibits J light /J dark ratio of 4.8 Â 10 14 and LDR of 293.55 dB at 2 W cm À2 in self-powered mode and are better than that of Gr-Si based heterojunction photodetector. 84,85 The photocurrent density J light and incident power P in satisfy the relationship 86…”
Section: Electrical Characterizationmentioning
confidence: 99%
“…3c shows the J light , J light /J dark ratio, and LDR for various P in values at zero-bias and 77 K. The device exhibits J light /J dark ratio of 4.8 Â 10 14 and LDR of 293.55 dB at 2 W cm À2 in self-powered mode and are better than that of Gr-Si based heterojunction photodetector. 84,85 The photocurrent density J light and incident power P in satisfy the relationship 86…”
Section: Electrical Characterizationmentioning
confidence: 99%
“…Another approach is to utilize interfacial oxide layers on photodiodes. Selvi et al demonstrated that such interfacial oxides increase the Schottky barrier height (SBH) and lead to an enhancement in photovoltage responsivity, particularly for low light intensities 31 . Complex nanotip patterning of substrates was employed to improve the photoresponse of G/Si Schottky diodes 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Diffraction limited spot sizes were ≈ 1µm and 2µm, respectively, and SPM measurements were carried out at an applied reverse bias voltage of V b = -2V. The laser light was chopped at a frequency f = 2kHz and the electrical signals recorded using a lock-in amplifier (Zurich Instruments HF2LI/HF2TA) [7]. Employed lock-in technique allows characterization of the photocurrent-magnitude and -phase to determine the absolute photoresponse as well as inferring time delays between optical excitation and electrical response of the devices.…”
mentioning
confidence: 99%
“…This inhomogeneity can be attributed to the non-uniform interface and quality of the GSi Schottky junction. Previous studies highlighted the importance and implications of the natural oxide layer formed between graphene and silicon [20,21] and the re-growth of this oxide layer after device fabriation [7]. The interfacial oxide layer thickness and quality influence the Schottky barrier height and with it the efficiency of conversion of infrared light into electrical current.…”
mentioning
confidence: 99%